2021
DOI: 10.3390/medicina57070652
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Mind-Body Interventions to Treat Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: Background and Objectives: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a chronic condition distinguished by disabling fatigue associated with post-exertional malaise, as well as changes to sleep, autonomic functioning, and cognition. Mind-body interventions (MBIs) utilize the ongoing interaction between the mind and body to improve health and wellbeing. Purpose: To systematically review studies using MBIs for the treatment of ME/CFS symptoms. Materials and Methods: MEDLINE, EMBASE, CINAHL, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 108 publications
0
14
0
Order By: Relevance
“…Evidence of systematic review for Qigong has shown to improve depression (27,28), and this study provided corresponding evidence for YJJQE. This finding might benefit from the fact that psychosomatic therapy has the dual mechanism of exercise and meditation that can relieve KOA pain and mood disorders (29,30). The underlying mechanism that physical exercise, combined with continuous cognitive challenge training, can maintain a new neuron pool experiences, more complex cognitive tasks, and even recruits new neurons to improve brain function (31).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of systematic review for Qigong has shown to improve depression (27,28), and this study provided corresponding evidence for YJJQE. This finding might benefit from the fact that psychosomatic therapy has the dual mechanism of exercise and meditation that can relieve KOA pain and mood disorders (29,30). The underlying mechanism that physical exercise, combined with continuous cognitive challenge training, can maintain a new neuron pool experiences, more complex cognitive tasks, and even recruits new neurons to improve brain function (31).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent review of meditation for post-viral fatigue (eg, ME/CFS) did not find significant differences at follow-up for any interventions lasting less than 8 weeks. 175 Interventions shorter than 8 weeks did not find changes in underlying biomarkers, immune markers, or neurocognitive functioning. The research appears to support bringing about positive biological processes in 8–12 weeks of meditation (see Tables 1 and 2 ).…”
Section: Intervention Duration Parametersmentioning
confidence: 92%
“…In addition, a recent review of meditation for post-viral fatigue (eg, ME/CFS) concluded that the basic symptoms were shown to be improved in patients receiving mind-body interventions. 175 Mahendru 4 found that those provided meditation after SARS-CoV-2 infection reported improvement in multiple sleep indicators. Bushell et al 8 review suggested that meditation interventions were of importance to moderating immune function, specifically for SARS-CoV-2 infection and Long COVID.…”
Section: Meditation For Pasc and Me/cfsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found general improvements in these outcome parameters. However, these findings must be regarded as provisional, due to small sample sizes, heterogeneous diagnostic criteria, and the possibility of various biases [42].…”
mentioning
confidence: 97%